Perception of students of the Degree in Tourism of a Higher Education Institution regarding the importance of a foreign language: English - Leite, Sónia (2022)
Being the most widely used global language, English has been exerting a tremendous influence around the world in various spheres of our lives. These comprise, among others, travel, tourism, and hospitality industry, in all of wich the use of English has become an imperative need. With its ever-growing importance, the role of English in travel, tourism and hospitality industry has been assuming greater significance, and also undergoing some functional changes. [...]